Exploring Racial Differences Surrounding Prostate Cancer Screening: Beliefs and Attitudes in Community Dwelling Men Attending an Urban Men's Health Event. Issue 6 (November 2018) - Hewitt, Timothy; Killinger, Kim A.; Hiller, Spencer; Boura, Judith A.; Lutz, Michael
The purpose of the study was to explore attitudes/beliefs in men attending an urban health fair to explore barriers to prostate cancer (PCa) screening. Five hundred and forty-four men attending the PCa booth at the fair in 2014 or 2015 completed questionnaires about PCa. Data were examined using Pearson's χ 2, Fisher's Exact, and Wilcoxon rank tests after grouping men by African American (AA) and non-African American ethnicity. Three hundred and twenty-six (60%) men were AA and two hundred and eighteen (40%) were non-AA (89% white). Median age (54 vs. 56 years) and prior PCa screening were similar between AA and non-AA; income ( p = .044) and education ( p = .0002) differed. AA men were less likely to have researched prostate-specific antigen (PSA) on the internet ( p = .003), but more used TV ( p = .003) and media ( p = .0014) as information sources. Family members had a stronger influence over screening decisions for AA men ( p = .005). After reading PSA information, AA men were more likely to still be confused ( p = .008). A higher proportion of AA men were less worried about dying from PCa ( p = .0006), but would want treatment immediately instead of watchful waiting ( p < .0001). Interestingly, a higher proportion of AA men indicated that they would prefer not to know if they had PCa ( p = .001). Ultimately, more AA men had a PSA done (98.4% vs. 95.1%; p = .031). When considering screening eligible men, a higher proportion of AA men had an abnormal PSA (13.1% vs. 5.3%; p = .037). AA men's beliefs surrounding PCa differ from non-AA men, and should be considered when developing culturally appropriate education, screening, and treatment strategies for this group.